PENERAPAN METODE PEMBELAJARAN SELF ORGANIZED LEARNING ENVIRONMENT DALAM MENGEMBANGKAN SOFT SKILL MAHASISWA - Ketut, Nurhayanti; Astri Pramitari, I Gusti Ayu; Suwintana, I Ketut; Budiada , I Made (UHN IGB Sugriwa Denpasar, 2023)
This research examines the application of the self-organized learning environment learning method in an effort to develop the soft skills of students in the Applied Managerial Accounting Undergraduate Study Program at the Bali State Polytechnic. This research method is descriptive qualitative using interview and questionnaire data collection techniques for 96 respondents. The result is a self-organized learning environment learning method that combines internet technology as a reference source for students with lecturers as a reference source that can develop students' soft skills such as having an initiative, independent, trustworthy and communication skills.